PERANCANGAN PARAMETER PI-DIGITAL DENGAN METODE RST-POLE PLACEMENT PADA DIRECT TORQUE CONTROL MOTOR TRAKSI INDUKSI TIGA FASA - Nur Hidayatus Safitri; Moch. Rusli; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
In the current development of industrial technology, electricity has been used as the prime mover. One of them is an electric motor, the most widely used is an induction motor. This is because induction motors have advantages in easier maintenance, relatively affordable prices, sturdy construction, and more reliable performance. Examples of the use of induction motors are in modes of transportation, both land, sea and air. However, induction motors still have a weakness which lies in the speed of themotor which is complicated to control. So the speed control research was carried out using the Direct Torque Control (DTC) method. To set the condition of the inverter switching using Space Vector Modulation (SVM). Speed, torque and flux control is carried out with a PI controller, where the PI parameters are determined using the RST-pole placement tuning method. Pole determination is based on the desired design performance criteria. The results of PI parameter on speed, torque, and flux arerespectively Kpω = 1277,59 and Tiω = -0,96, KpT = 8,4 and TiT = -0,2, Kpψ = 67,7 and Tiψ = 0,17. After testing, under no-load condition and a set point of 157 rad/s the system was able to reach a steady state with a steady state error of 0,6% within a settling time of 0,25 seconds. Under conditions of variation in load of 100 Nm, 200 Nm, 300 Nm, the system was able to reach steady state with steady state errors of 0,6%, 0,9%, and 1,2% in settling times of 0,25 seconds, 0,27 seconds, and 0,28 seconds, respectively. Keywords: Three Phase Induction Traction Motor, Direct Torque Control, Space Vector Modulation, PI-Digital Controller, RST Controller. DAFTAR PUSTAKA[1] S. E. Nugroho, W. Aribow, Ibrohim and A. C. Hermawan, "SISTEM PENGENDALIAN KECEPATAN MOTOR TIGA FASA MENGGUNAKAN METODE DIRECT TORQUE CONTROL 8 (DTC)," Jurnal Teknik Elektro, vol. X, no. 1, pp. 81-90, 2021.[2] K. R. S. Suda, E. Purwanto, B. Sumantri, H. H. Fakhruddin, A. A. Muntashir and M. R. Rusli, "PENGATURAN KECEPATAN MOTOR INDUKSI 3 FASA DENGAN MENGGUNAKAN PEMODELAN SISTEM (DTC) DIRECT TORQUE CONTROL," Jurnal Pendidikan Teknologidan Kejuruan, vol. XVIII, no. 2, pp. 237-248, Juli 2021.[3] A. Poorfakhraei, M. Narimani and A. Emadi, "A Review of Modulation and Control Techniques for Multilevel Inverters in Traction Applications," IEEE Access, Hamilton, 2021. [4] I. N. W. Satiawan, I. B. F. Citarsa and Supriono, "Perbandingan Kinerja Teknik Modulasi Inverter Dua-Level untuk Pengaturan Kecepatan Motor Induksi TigaFase," elektronik Jurnal Arus Elektro Indonesia, 2015.[5] Y. Satyanarayana and A. Srujana, "Speed Control of Induction Motor using Fuzzy PI Controller Based on Space Vector PulseWidth Modulation," International Journal Of Computational Engineering Research, pp. 1203-1209, September 2012.[6] I. D. Landau, "The R-S-T digital controller design and applications," Control Engineering Practice, pp. 155-165, 1998. [7] O. C. Sekhar, S. Lakhimsetty and A. H. Bhat, "A Comparative Experimental Analysis of Fractional Order PI Controller Based Direct Torque Control Scheme for Induction Motor Drive," International Transactions on Electrical Energy Systems, pp. 1-19, 2020.[8] R. Garg, P. Mahajan, N. Gupta and H. Saroa, "A Comparative Study between Field Oriented Control and Direct Torque Control of AC Traction Motor," in IEEE International Conference on Recent Advances and Innovations in Engineering, Jaipur, 2014.[9] M. Yusuf, V. Prasetia, S. D. Riyanto and A. A. Rafiq, "Desain Simulasi Sistem Pengaturan Motor Induksi Tiga Fasa dengan Switching Space Vector Pulse Width Modulation," ECOTIPE, vol. VI, no. 1, pp. 24-31, 2019.[10] D. w. Saputra, Design KOntrler PI Digital Berbasis Kriteria Integral Error Kuadratik pada Sistem Kontrol Kecepatan Motor DC,Malang: Skripsi, 2017.[11] I. D. Landau and G. Zito, DIGITAL CONTROL SYSTEMS : Identification, design and implementation, Berlin: Springer, 2006.[12] N. Pimkumwong and M.-S. Wang, "Direct Torque Control of Three-Phase Induction Motor based on Constant Voltage perFrequency Control with Simple Controller," in 15th International Conference on Electrical Engineering/Electronics, Computer,Telecommunications and Information Technology (ECTI-NCON2018), Taiwan, 2018.[13] S. Enache, A. Campeanu, I. Vlad, R. Zlatian and M. A. Enache, "Dynamic Analysis of New Induction Motor for Electrical Traction," in International Symposium on Power Electronics, Electrical Drives, Automation and Motion, Craiova, 2020.[14] K. L. Shi, T. F. Chan, Y. K. Wong and S. L. Ho, "Modelling and Simulation of Direct Self-Control Systems," in Int. J. Engng Ed,Kowloon, 2003.[15] S. Enache, A. Campeanu, I. Vlad and M. A. Enache, "Particular Dynamic States of Railway Traction Asynchronous Motors,"in The XIth International Symposium on Advanced Topics in Electrical Engineering, Bucharest, 2019.[16] N. R. Mulyawan, S. Yahya and A. R. AlTahtawi, "Pemodelan Kecepatan Motor Induksi Tiga Fasa Dengan Metode Proportional Integral Anti Wind Up (PiAw)," in Prosiding SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), Sukabumi, 2020.